Development and Validation of Science Self Efficacy Scale (SSES) for Secondary School Students - Shivani (JOURNAL OF INDIAN EDUCATION, 2023)
The research study was taken to develop a suitable and reliable scale for measuring self efficacy belief in science subject among secondary school students. In this research study, a collection of 55 items were constructed to develop the ‘Science Self Efficacy Scale’ (SSES) based on the literature review related to discussion with experts. The items were arranged into five dimensions of science self efficacy, namely, ‘self confidence’, ‘self regulation’, ‘self concept’, ‘perceived science efficacy’ and ‘outcome expectancy’. These items were graded on five point Likert scale. The process of validation was accomplished with 300 students of 14–15 years age group, studying science as a subject, and selected randomly from Government schools of Haryana, India. The process of item analysis was done by calculating t-values. Fourteen items of the scale were dropped, and finally, 41 items were kept. The calculated value of Cronbach’s alpha came out to be 0.86 and for the split-half method, it was 0.76. The construct validity of the scale was determined by calculating the co-efficient of correlation between the scores of this scale and the score obtained by using ‘Self Efficacy Scale’ (SES) by Singh and Narain, 2014. The percentile norms for the scale were obtained after validating the normality score by Q-Q plot. The result suggests that SSES may be a helpful tool for future research to assess self belief in persons, particularly in science subject. The SSES scale is relevant to students, psychologists and school teachers. This tool can be used for evaluation and understanding of self efficacy level in science, thereby helping them in planning and implementing different kinds of strategies for enhancing their self efficacy level.